Making Ecobrick: Powerful Reduce Plastic Trash - Zuska, Fikarwin; Naria, Evi; Febira, Noly; Aulia, Fikri (Talenta Publisher, 2023)
Plastic waste has created tiny particles called microplastics. Microplastics threaten life on this earth. Until now, the reduction of plastic waste has not been significant because it is not fast compared to its production. Only a few plastic producers want to intervene in this matter by withdrawing their products which have become waste from consumers. In general, consumers are left responsible for managing plastic packaging waste made by producers. Therefore, with the existing limitations, the residents, after being empowered with their assistants, made efforts to deal with plastic waste by using eco-bricks. As a result, one ecobric prevents 2 ounces of plastic waste from becoming pollutants. The more ecobric is made, then purchased at an agreed price, the budget will be divided among less fortunate families.